PENINGKATAN KETERAMPILAN BERBICARA DALAM MEMPRESENTASIKAN TEKS EKSPLANASI MENGGUNAKAN MODEL PEMBELAJARAN TIME TOKEN ARENDS DI KELAS V SDN 18 AIR TAWAR SELATAN - Pradipta, Dyni Arrisky; Alwi, Nur Azmi; Chandra, Chandra; Rahmi, Gita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research began with the limited speaking ability of students when presenting explanatory texts in grade V of SDN 18 Air Tawar Selatan. This occurs because the learning process tends to focus on educators, and the lack of students' abilities in speaking aspects, as well as low fluency and confidence when expressing opinions. The purpose of this study is to explain how students' speaking skills improve using the Time Token Arends model. This study uses the Classroom Action Research (CAR) method which combines qualitative and quantitative approaches. The research activities were carried out in two cycle which included planning, action, observation, and review. The research information collection technique was carried out through tests and non-tests. Participants in this study were 19 grade V students of SDN 18 Air Tawar Selatan. The study findings showed positive developments in every aspect of learning. The assessment of the In-Depth Learning Implementation Plan (RPPM) increased from 91,06% (SB) in the first cycle to 96,42% (SB) in the second cycle. Teacher and student activity also improved, from 85,93% (B) to 96,87% (SB). Students' speaking skills improved from 72,47 (C) in the first cycle to 87,27 (B) in the second cycle. There were improvements in pronunciation, grammar, vocalization, fluency, comprehension, and speaking confidence. Therefore, the Arends Time Token Learning Model has been proven to help students improve their speaking skills, especially when presenting explanatory texts